2021
DOI: 10.1088/1361-6463/ac1d14
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the first Townsend ionization coefficient in mixtures of Ar and N2

Abstract: Mixtures of Ar with N 2 are relevant for many areas of plasma applications. In particular, modeling of atmospheric pressure plasma jets for biomedical applications requires precise knowledge of fundamental gas parameters such as the Townsend ionization coefficient α. This study determines α in mixtures of Ar with N 2 in a dark non-self-sustaining Townsend discharge. The discharge current versus electrode spacing was measured in the absolute pressure range of 10-800 Torr and reduced electric field strength E/N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…The current density of a normal glow discharge is expressed as follows: where jng is the current density; 𝜀 is the dielectric constant; 𝛾 is the secondary electron emission coefficient; 𝐸 𝑝 ⁄ is the reduced electric field in the vicinity of the cathode surface; 𝛼 is the Townsend ionization coefficient; 𝑣 is the ion drift velocity, and 𝐸 𝑝 ⁄ is the reduced electric field [50]. The 𝛼 of argon is almost one-order higher than that of nitrogen, around 200 Td in a reduced electric field [51]. In other words, the higher applied voltage at nitrogen gas is more necessary than that at argon gas for the same Townsend coefficient value.…”
Section: Electrical Characteristics Of Glow Plasmamentioning
confidence: 99%
“…The current density of a normal glow discharge is expressed as follows: where jng is the current density; 𝜀 is the dielectric constant; 𝛾 is the secondary electron emission coefficient; 𝐸 𝑝 ⁄ is the reduced electric field in the vicinity of the cathode surface; 𝛼 is the Townsend ionization coefficient; 𝑣 is the ion drift velocity, and 𝐸 𝑝 ⁄ is the reduced electric field [50]. The 𝛼 of argon is almost one-order higher than that of nitrogen, around 200 Td in a reduced electric field [51]. In other words, the higher applied voltage at nitrogen gas is more necessary than that at argon gas for the same Townsend coefficient value.…”
Section: Electrical Characteristics Of Glow Plasmamentioning
confidence: 99%
“…The density-reduced Townsend ionization coefficient α/N was determined in low-current electrical discharges under SST conditions many times in the past using the similar approach: usually the dependence of ln (I/I 0 ) on the electrode gap distance is measured for various E/N values, where I is the discharge current and I 0 is the initial current at the cathode. Examples include the recent measurements of α/N in gas mixtures of He with N 2 [109], Ar with N 2 [110] as well as the recent measurements of α eff /N in C5 perfluorinated ketone and its mixtures with air [111]. In the present modeling of an idealized SST setup, we have observed that the agreement between the two methods is very good, except for the lowest values of E/N, where the number of ionizing collisions is significantly reduced.…”
Section: Electron Swarm Transport Properties In An Idealized Sst Setupmentioning
confidence: 99%